Upaya Meningkatkan Hasil Belajar Matematika Melalui Penerapan Model Pembelajaran Group Investigation - Nelson Tambunan (Smart Education, 2020)
Abstract: This research is a classroom action research, with the research subjects of class X IPA SMA Negeri 2 Lintongnihuta, totaling 29 people. This study's object is the student learning outcomes during the implementation of learning by applying the Group Investigation learning model on the Equation and Inequality of Absolute Value in Class X IPA SMA Negeri 2 Lintongnihuta. The instrument used was a test consisting of 5 items. The results showed that in cycle I, there were 22 students completed (78.57%). The percentage of student activity is 78.57% in the excellent category. In the second cycle, there were 27 students (96.43%) who completed. The percentage of student activity is 96.43% in the excellent category. So there is an increase in student learning outcomes through the application of the Group Investigation learning model on the subject of the Equation and Inequality of Absolute Values at SMA Negeri 2 Lintongnihuta. Keywords: absolute value; group investigation; equations and inequalities Abstrak: Penelitian ini merupakan penelitian tindakan kelas, dengan subjek penelitian siswa kelas X IPA SMA Negeri 2 Lintongnihuta yang berjumlah 29 orang. Objek dalam penelitian ini adalah hasil belajar siswa selama pelaksanaan pembelajaraan melalui penerapan model pembelajaran Group Investigation pada materi Persamaan dan Pertidaksamaan Nilai Mutlak di Kelas X IPA SMA Negeri 2 Lintongnihuta. Instrumen yang digunakan adalah tes yang terdiri dari 5 butir soal. Hasil penelitian menunjukkan bahwa pada Pada siklus I terdapat 22 orang siswa tuntas (78,57 %). Persentase aktivitas siswa sebesar 78,57% berada pada kategori baik. Pada siklus II terdapat 27 orang siswa (96,43%) tuntas. Persentase aktivitas siswa sebesar 96,43% berada pada kategori baik. Jadi ada peningkatan hasil belajar siswa melalui penerapan model pembelajaran Group Investigation pada pokok bahasan Persamaan dan Pertidaksamaan Nilai Mutlak Di SMA Negeri 2 Lintongnihuta. Kata kunci: group investigation; nilai mutlak; persamaan dan pertidaksamaan